PENINGKATAN KETERAMPILAN BERBICARA MELALUI MODEL TALKING STICK PADA SISWA KELAS IV SDN 02 CUPAK TANGAH KOTA PADANG - Kinanti, Ajeng; Adrias, Adrias; Chandra, Chandra; Yenti, Yesni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low speaking skills of fourth-grade students at SDN 02 Cupak Tangah, Padang City, particularly in expressing opinions, using appropriate language, and speaking fluently. The purpose of this study was to improve students’ speaking skills through the implementation of the Talking Stick learning model. This research employed Classroom Action Research (CAR) conducted in two cycles, where each cycle consisted of planning, action, observation, and reflection stages. The subjects of this study were fourth-grade students of SDN 02 Cupak Tangah, Padang City. Data were collected through observation and speaking performance assessment based on five aspects: argumentation skills, comprehension, accuracy of words and sentences, style and delivery, and fluency. The results showed a significant improvement in students’ speaking skills in each cycle. The average score increased from 69.44% in Cycle I Meeting 1 to 78.89% in Cycle I Meeting 2, and further improved to 86.30% in Cycle II. The percentage of students achieving mastery learning also increased from 44.44% to 66.67%, and reached 85.19% in Cycle II. It can be concluded that the Talking Stick model is effective in improving students’ speaking skills.